Types of information warfare and examples of malicious programs of information warfare - Damjanović, Dragan Z. (Vojnotehnički glasnik / Military Technical Courier, 2017)
The possibilities of the information management system are unimaginable. "Information warfare" (IW), defined as a targeted effort to undermine and neutralize hostile command and control systems for the purpose of protecting and coordinating the activities of command and control systems of friendly forces, is a frequently used term. Most of modern political and military systems of command and control are based on high speeds of computer-based communication. Hence, the information infrastructure is the "infomercial" arena in which information warfare is conducted. Every system or a person that forms part of this sphere is a potential target in IW. The form of information warfare is the way of its exposure and it is expressed through the structure of events and activities related to the processes that take place in it. This means that the form of information warfare is a special feature that distinguishes it qualitatively from other forms. It is evident that information warfare dramatically affects the mode of war, regardless of whether it is only an evolutionary period or represents a revolutionary development.